Women and Money: Unique Issues – Selecting Your Financial Professional Team - Brenda C. Williams; Diann Douglas; Martie Gillen; Lynda Spence (EDIS)
On your road to building wealth, you may choose to engage financial professionals for guidance. Seeking out professional advice will include fees and expenses, so use care when selecting the appropriate services. There is a variety of financial professionals to choose from, including financial planners, investment specialists, accountants, attorneys, insurance agents, and bankers. Understanding the roles, expertise, and credentials of these individuals can help you select the most appropriate individual or team for your specific financial needs. This 4-page fact sheet was written by Brenda C. Williams, Diann Douglas, Martie Gillen, and Lynda Spence, and published by the UF Department of Family Youth and Community Sciences, July 2013.